The Effectiveness of Health Education on Breast Self-Examination (S A D A R I) on Young Women's Knowledge About Early Detection of Breast Cancer - Titania Aurilia (STIKes Payung Negeri Pekanbaru, 2022)
The most common cancer in women is breast cancer, which is a malignant tumor that grows in the breast tissue, which includes the mammary glands, milk ducts, fatty tissue, and connective tissue in the breast. This study aims to determine the effectiveness of breast self-examination health education (BSE) on the knowledge of young women about early detection of breast cancer. This study used a quasi-experimental design with a pretest and posttest approach with one group design. The purposive sampling method in this design did not have a comparison group (control) with a sample of 34 young women at the Payung Sekaki Health Center, Payung Sekaki District. The instrument is a knowledge questionnaire of Breast Self Examination (BSE) as an early detection of breast cancer. The statistical test used in this study was the Wilcoxon test. This study found that there was an effect of health education on breast self-examination (BSE) on young women's knowledge about early detection of breast cancer with a P value (0.000) which means P Value < (0, 05). The measuring instrument used is a questionnaire that has been tested for validity and reliability. The analysis used is univariate and bivariate analysis with Wilcoxon test. The results of the Wilcoxon test showed P value (0.000), which means P Value < (0.05) . There is an effect of health education on breast self-examination (BSE) on the knowledge of young women about early detection of breast cancer. The results of this study can be one of the nursing interventions in increasing the knowledge of young women in early detection of breast cancer.